2020
DOI: 10.1002/ncp.10472
|View full text |Cite
|
Sign up to set email alerts
|

Narrowing the Protein Deficit Gap in Critically Ill Patients Using a Very High‐Protein Enteral Formula

Abstract: Background: Protein deficits have been associated with longer intensive care unit (ICU) stays and increased mortality. Current view suggests if protein goals are met, meeting full energy targets may be less important and prevent deleterious effects of overfeeding. We proposed a very-high protein (VHP) enteral nutrition (EN) formula could provide adequate protein, without overfeeding energy, in the first week of critical illness. Methods: This was a retrospective study of medical/surgical ICU patients receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(153 reference statements)
1
0
0
Order By: Relevance
“…Our results are similar to observational data that assessed the feasibility of formulas with higher enteral protein 26 , as well as a previously published, smaller, randomized trial that found separation in enteral protein dose was achievable while maintaining blinding 27 . We now provide evidence that treatment separation is possible in a heterogeneous population of ICU patients over a prolonged period during rapid recruitment.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are similar to observational data that assessed the feasibility of formulas with higher enteral protein 26 , as well as a previously published, smaller, randomized trial that found separation in enteral protein dose was achievable while maintaining blinding 27 . We now provide evidence that treatment separation is possible in a heterogeneous population of ICU patients over a prolonged period during rapid recruitment.…”
Section: Discussionsupporting
confidence: 89%